Exchange rate volatility and the returns on diversified South African investment portfolios - Mulamu, Murendeni (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Globalisation has made it much easier to invest in foreign countries. This creates endless options accessible to investors, including exploiting opportunities for investment in international economies. Although foreign investment portfolio diversification provides significant opportunities for financial returns, exchange rate volatility may play a prominent role when investing in foreign markets. Since the introduction of a floating exchange rate system, together with the inflation-targeting monetary policy framework in South Africa, there has been significant volatility in the exchange rate, far more than during the previous dispensations. This, however, creates a strong need to consider how the unpredictable nature of the exchange rate affects these investments. The purpose of this study is to analyse the effect of exchange rate volatility on the returns on diversified South African investment portfolios. This research examined whether there is a homogenous relationship between South African (domestic) portfolios and the internationally diversified portfolios. In addition, the study investigated the long-run relationship between the exchange rate volatility and both domestic portfolios and the internationally diversified portfolios for the period 2007-2019. To achieve these goals, a panel ARDL model was employed. This study found that exchange rate volatility does not account for a significant portion of returns on investment portfolios fluctuations. Moreover, the relationship is not homogenous because returns on domestic investment portfolios react positively to the exchange rate volatility, whereas returns international investment portfolios respond negatively/positively to the exchange rate volatility depending on whether the relationship is short or long run. This study will contribute to the existing literature, and it is important for investors intending to diversify their investment portfolios both domestically and internationally using different mutual funds in South Africa.
Keywords: Foreign exchange rates -- South Africa; Rate of return; Investments; GARCH model; Regression analysis; Autoregressive distributed lag (ARDL) model